Physical and performance variables for talent identification in water polo - Viero, V.; Triossi, T.; Bianchi, D.; Campagna, A.; Melchiorri, G. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The aim of this work was to compare anthropometric and general physical performance variables in young water polo athletes of three competitive levels, to identify the characteristic qualities and, therefore, the best variables for the identification of talent. METHODS: Fifty-seven young male water polo players between 12 and 14 years old were recruited for the study: 18 were recreational level (REC), 18 sub-elite level (SE) and 21 elite level (EL). To assess anthropometric characteristics the following measurements were used: body mass, height, waist circumference, hip circumference, chest circumference and arm span. Five general performance measures were used: counter movement jump (CMJ), triple hop jump (THJ), push up, chin up and sit up. Relative age was assessed. RESULTS: The whole sample was homogeneous by age (REC 13.1±0.4, SE 13.2±1.0, EL 13.3±0.7 years old) but not in terms of relative age: most of the members of the SE and EL groups were born in the first half of the year. Body mass values (REC 48.2±11.6, SE 59.3±11.6, EL 69.1±4.2 kg) show statistically significant differences between all three competitive levels (REC vs. SE P=0.007, REC vs. EL P=0.001, SE vs. EL P=0.009). As regards the other anthropometric measurements differences were mainly observed between REC and the two other groups: SE and EL had statistically significant higher values in almost all of the measurements carried out. Among the performance measures, lower limb strength (CMJ and THJ) seems to better differentiate between groups: REC group had lower values than the others and EL had the highest values. CONCLUSIONS: Anthropometric characteristics are useful to distinguish the basic level of youth categories from higher competitive levels and should be used for talent selection. The performance results confirm that the subjects` capacity to be trained and sporting practice are essential to reach the elite level.